Prinsip Keseimbangan pada Sektor Pariwisata Berkelanjutan di Lombok, Nusa Tenggara Barat - Dewi Saraswati; Muhammad Sarjan (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to analyze the implementation of the principle of balance (natural harmony) in natural resource management in the sustainable tourism sector in Lombok, West Nusa Tenggara. The study focuses on the meaning of balance between economic, social, cultural, and environmental aspects as the basis for sustainable tourism development. The method used is a qualitative descriptive approach through a systematic literature review conducted through the search and analysis of scientific literature, regional policies, and relevant empirical research results. The results show that the implementation of the principle of balance has been attempted through the development of community-based tourism, the utilization of ecological potential according to carrying capacity, and the implementation of policies and collaboration between stakeholders. However, the implementation of the principle of natural harmony still faces obstacles such as development pressures, environmental degradation, dependence on external assistance, and limited institutional capacity. In addition, this study found that community-based strategies and environmental technologies, including the use of remote sensing and Geographic Information Systems (GIS), have the potential to strengthen sustainable tourism governance and increase the effectiveness of natural resource monitoring. This research provides a conceptual contribution to strengthening adaptive, participatory, and long-term sustainability-oriented tourism development policies and practices in Lombok.